Central role of ultrasound in the evaluation of testicular function and genital tract obstruction in infertile males. (18th June 2021) - Garolla, Andrea; Grande, Giuseppe; Palego, Pierfrancesco; Canossa, Andrea; Caretta, Nicola; Di Nisio, Andrea; Corona, Giovanni; Foresta, Carlo
Abstract: Background: Scrotal color Doppler ultrasonography and transrectal ultrasonography provide crucial information about the clinical status of testes and male accessory glands. Objective: To analyze the impact of ultrasound in the evaluation of infertile males. Materials and Methods: A total of 1120 records from infertile men were retrospectively evaluated (from January 2016 up to June 2020). Data on physical examination, semen analysis, sperm culture, scrotal color Doppler ultrasonography and transrectal ultrasonography, as well as sex hormones were analyzed. Among them, 238 reports from oligozoospermic/azoospermic infertile patients (P) fulfilling the inclusion criteria were considered for data analysis. Patients were subdivided into two groups according to follicle‐stimulating hormone (FSH) values (Pa with FSH < 8 U/L and Pb with FSH ≥ 8 U/L). Sixty‐three fertile volunteers (mean ± SD years) were enrolled as controls (C). Results: A higher prevalence of ultrasound abnormalities was recorded in P compared to C. Pb group had significantly lower bitesticular volume compared to Pa and C. Pa had a higher prevalence of transrectal ultrasonography abnormalities than Pb (69.9% vs. 38.4%), whereas Pb had a higher prevalence of abnormalities at scrotal color Doppler ultrasonography (60.0% vs. 28.3%, both p < 0.01). Bitesticular volume was inversely proportional to the number of altered seminal parameters and able to predict gonadotropin levels. A bitesticular volume <17 cc was associated with a higher risk of azoospermia (odds ratio = 1.799). Intratesticular vascularization was inversely correlated with gonadotropin levels and directly correlated with sperm count. A higher prevalence of prostate and seminal vesicle alterations was detected in patients and in Pa group, when compared with Pb group. Discussion and Conclusion: Ultrasound abnormalities are correlated with seminal parameters and may guide the clinician in the diagnostic workflow of male infertility, suggesting spermatogenesis impairment or genital tract obstructions.